Hemolymph ecdysteroids and molt cycle in males and females of Siriella armata M.-Edw. (Crustacea: Mysidacea): Possible control by the MI-ME X-organ of the eyestalk. - CUZIN-ROUDY-J; STRAMBI-C; STRAMBI-A; DELBECQUE-J-P (GENERAL AND COMPARATIVE ENDOCRINOLOGY 74(1): 96-109, 1989)
Hemolymph ecdysteroids were quantified by radioimmunoassay (RIA) at successive stages of the molt cycle in the mysid Siriella armata. Profiles showed a single pea during premolt, at stage D1 for males, and D2 for reproducing females who displayed ecdysteroid levels 10 times higher than males. Titers were also measured for individuals which had been molt inhibited by early electrocauterization of the eyestalk MI-ME X-organ. In the cases of total inhibition of molt preparation, the ecdysteroid peak was suppressed. It was displaced toward the end of the cycle when only ecdysis was inhibited. Ecdysone and 20-hydroxyecdysone were characterized in the hemolymph of both sexes using high-pressure liquid chromatography followed by RIA. High-polarity products, abundant in the female hemolymph, were resolved into 20-hydroxy ecdysone and ecdysone by enzymatic hydrolysis and thin-layer chromatography. The quantitative and qualitative variations ofecdysteroid in the different situations (male or female, normal or inhibited cycles) are presented in relation to apolysis, epidermic activity, ecdysis, and secondary vitellogenesis in females, emphasizing the importance not only of ecdysteroids, but also of the MI-ME X-organ in monitoring molt and blood preparation in mysids.
NeMys doc_id: 3761